School is the education of students path to success - Nagymzhanova Каракат; Shonova Алия (Рroblems of engineering and professional education, 2023)
The article discusses the ways of succeeding of a learnen in learning process. It also shows a learner’s actuality in reaching success, current state and main methods. In addition to this, it revcals necessary mechanisms of a learner’s succeeding.